THE CURRENT RESEARCH TREND OF ISLAMIC EDUCATION IN INDONESIA PESANTREN AND ITS PROPERTIES - bahrul ulum; nanang qosim; Sanju Kumar Singh (Piwulang: Jurnal Pendidikan Agama Islam, 2023)
Globalization disrupted the value of norms and religion in young generations. Islamic education in pesantren could become a medium to increase the awareness of people about the importance of Islamic principles in their lives. However, not many previous studies are well-known globally by overseas researchers and academicians. This study has the purpose of observing the development of research about Islamic education in pesantren in Indonesia. This paper used bibliometric analysis to collect and analyze the secondary data of previous studies from the Scopus website. There were 113 documents found in Scopus from 1994-2023. The data were analyzed using two software, Vosviewer and R Studio. The analysis was divided into 2, citation analysis and mostly used word analysis. The result showed that the most current words used as the author’s keywords were pesantren education, accommodation, management, effective schools, conservative, and developing countries. No word related to technology or digitalization was used either in the author’s keyword or abstract of previous studies that were reflected as the current situation of the 4th industrial revolution today. Moreover, the affiliation of the author with the highest number of citations was the UK. Indonesian authors were ranked 2nd, 3rd, 3rd, and 5th. There were also some authors whose affiliations were not countries with Muslims as the majority of the citizens.Globalisasi mendisrupsi nilai norma dan agama pada generasi muda. Pendidikan Islam di pesantren dapat menjadi media untuk meningkatkan kesadaran masyarakat akan pentingnya prinsip-prinsip Islam dalam kehidupan mereka. Namun, tidak banyak penelitian sebelumnya yang dikenal secara global oleh peneliti dan akademisi luar negeri. Penelitian ini bertujuan untuk mengamati perkembangan penelitian tentang pendidikan Islam di pesantren di Indonesia. Makalah ini menggunakan analisis bibliometrik untuk mengumpulkan dan menganalisis data sekunder penelitian sebelumnya dari situs Scopus. Terdapat 113 dokumen yang ditemukan di Scopus dari tahun 1994-2023. Data dianalisis menggunakan dua perangkat lunak, Vosviewer dan R Studio. Analisisnya dibagi menjadi 2, analisis kutipan dan sebagian besar menggunakan analisis kata. Hasil penelitian menunjukkan bahwa kata-kata terkini yang dijadikan kata kunci penulis adalah pendidikan pesantren, akomodasi, manajemen, sekolah efektif, konservatif, dan negara berkembang. Tidak ada kata terkait teknologi atau digitalisasi yang digunakan baik dalam kata kunci penulis maupun abstrak penelitian terdahulu yang mencerminkan situasi revolusi industri ke-4 saat ini. Apalagi afiliasi penulis dengan jumlah sitasi terbanyak adalah Inggris. Pengarang Indonesia menduduki peringkat ke-2, ke-3, ke-3, dan ke-5. Ada juga beberapa penulis yang afiliasinya bukan pada negara yang mayoritas penduduknya beragama Islam.